2022
DOI: 10.1002/pbc.29970
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus for management of GI bleeding in blue rubber bleb nevus syndrome: A case series

Abstract: Blue rubber bleb nevus syndrome (BRBNS) commonly presents with anemia from bleeding gastrointestinal (GI) vascular malformations. Management is highly variable, as no consensus guidelines for medical treatment currently exist. Sirolimus has been used in BRBNS to decrease GI bleeding and seems well tolerated, though questions remain regarding dosing, duration of therapy, and adverse effects. Here, we report our single‐center experience of four pediatric patients with BRBNS who were successfully treated with sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Additionally, GI lesions are more prone to underhand symptoms leading to diagnostic delays. Medical treatment with Sirolimus seems promising, especially when other therapies would be too aggressive or fail [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. In our case, a "dominant lesion" was detected at birth, as it generally happens, but it was resected before the diagnostic definition.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, GI lesions are more prone to underhand symptoms leading to diagnostic delays. Medical treatment with Sirolimus seems promising, especially when other therapies would be too aggressive or fail [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. In our case, a "dominant lesion" was detected at birth, as it generally happens, but it was resected before the diagnostic definition.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, there are no widely available systemic treatment options that can effectively reduce bleeding rates or stabilise anaemia in BRBNS. However, recent case series and systematic reviews have shown promising results with the use of mammalian target of rapamycin inhibitors such as sirolimus 11–13. These medications nonetheless have significant side effects, including bone marrow suppression and substantial immunosuppression 13.…”
Section: Discussionmentioning
confidence: 99%